Labor Market and Staff Competence in The Digital Economy (Eurasian Research Bulletin, 2025)
The article provides a comprehensive analysis of the changes occurring in the labor market with the transition to a digital economy, and how the introduction of digital technologies will lead to significant changes in the demand for personnel and requirements for specialists.